Impact of climate change and environmental adversities on maternal and fetal health: the role of clinical practices and providers in mitigating effects and prioritising women's health in the UK - Athina Samara; Athina Samara; Athina Samara; Thomas Hanton; Ranee Thakar; Ranee Thakar; Eric Jauniaux; Asma Khalil; Asma Khalil; Asma Khalil; Asma Khalil (Frontiers in Global Women's Health)
The climate crisis poses profound risks to women particularly during pregnancy. With rising global temperatures and increasing frequency of extreme weather events, there is an urgent need for health initiatives and guidelines tailored to the unique vulnerabilities of pregnant individuals. We conducted a review of English-language literature from 2000–2024 using PubMed, Scopus, and Web of Science, focusing on “climate change,” “pregnancy,” and “maternal health,” and included original studies, reviews. Relevant policy documents, including some published in 2025 were also included. We examine the multifaceted challenges posed by climate change, such as extreme weather events, water scarcity, malnutrition, and exposure to environmental pollutants like contaminated air and water, which directly and indirectly affect maternal and fetal health. The review explores the associations between these environmental stressors and adverse pregnancy outcomes, including preterm births, low birth weight, and developmental complications. These challenges are compounded in low-resource settings where healthcare infrastructure is limited, exacerbating inequities in maternal care. Furthermore, we focus on key areas for further investigation, including the long-term health effects of in-utero exposure to pollutants. The review addresses evidence-based strategies to reduce the environmental impact of healthcare through early interventions, innovation, and strengthened initiatives. It emphasises empowering healthcare professionals to educate others, raise awareness among policymakers, advocate for climate-conscious policies, and promote sustainable practices reducing the carbon footprint of the healthcare system, with a focus on the UK. In response to these pressing concerns, leading professional organizations, such as the Royal College of Obstetricians and Gynaecologists (RCOG) in the UK, and the American College of Obstetricians and Gynaecologists (ACOG) in the US, are prioritizing the intersection of climate change and women's health. Their initiatives, which aim to mitigate the climate-change impacts on pregnancies and fetal health by promoting research, raising awareness, and developing actionable strategies, are also highlighted. By amplifying awareness and global collaboration, the suggested strategies aim to protect maternal and fetal health in the face of an escalating climate crisis.